Post-COVID-19-Invasive Pulmonary Mycosis - Swain, Satish; Sharma, Kunal; Ray, Animesh; Vyas, Surabhi; Singh, Gagandeep; Joshi, Mohit; Jain, Deepali; Xess, Immaculata; Sinha, Sanjeev; Wig, Naveet (Libyan International Medical University Journal, 2022)
COVID-19 has been associated with myriad manifestations as well as adverse outcomes. One of the less commonly reported consequences of COVID-19 is the occurrence of secondary infections in patients suffering acutely from COVID-19 or in those recuperating. Secondary invasive fungal infections (IFIs) have also been observed earlier in other viral infections such as influenza, parainfluenza, and respiratory syncytial virus infections. Severe lung damage and immunologic derangement resulting from SARS-CoV-2 infection predispose to superinfections. Risk factors for secondary IFI includes immunologic derangement and immunoparalysis resulting from SARS-CoV-2 infection, neutropenia, or lymphopenia, poorly controlled diabetes, structural lung disease fungal colonization, and drugs such as corticosteroids or immunomodulators given as therapies for COVID-19. Invasive aspergillosis following COVID-19 is most commonly described fungal infection but other non-Aspergillus fungal infections (including mucormycosis) has also been reported. Herein we describe two interesting cases of secondary infections developing in patients beyond the acute phase of COVID-19 who had similar presentations but with different diagnoses and requiring different management strategies. Patient in case 1 developed COVID-19-associated subacute invasive pulmonary aspergillosis (SAIA) and patient in case 2 had COVID-19 associated pulmonary mucormycosis (CAPM). We have also described the various postulated immune-pathogenesis of the super-added fungal infections in COVID-19 patients.
Keywords: COVID-19; mucorales; aspergillosis; immune dysfunction